Program Posyandu Plus: Peningkatan Pengetahuan Ibu Hamil Tentang Kesehatan Reproduksi - Ula, Zumrotul; R, Rahmaniyah; Veradilla, Veradilla; Andriani, Fitri; Arnianti, Arnianti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Posyandu (Integrated Health Post) is a form of community-based health service that plays a crucial role in improving maternal and child health. However, pregnant women's limited knowledge about reproductive health remains a barrier to preventing pregnancy and childbirth complications. The Posyandu Plus program is an innovation in community service activities, adding educational and counseling sessions specifically on reproductive health for pregnant women. This activity was implemented through outreach, interactive discussions, and simulations. Results indicate an increase in pregnant women's understanding of the importance of self-care, pregnancy danger signs, balanced nutrition, and safe birth planning. This program is expected to be sustainable and become a model for community empowerment in supporting maternal health.